Chemical synthesis, characterization and theoretical investigations of stannite phase CuZn2AlS4 nanocrystals. (18th November 2015) - Ghosh, Anima; Thangavel, Rajalingam; Gupta, Arunava
Abstract : The stannite-phase CuZn2 AlS4 nanocrystals strongly absorb at visible wavelengths, which is suitable for solar energy material applications. Abstract : Stannite phase CuZn2 AlS4 (CZAS) nanocrystals have been grown for the first time using hot injection and hydrothermal processes. As-synthesized nanocrystals in the shape of nanowires (from a hot injection process) and nanoplates (from a hydrothermal process) show band gaps of 1.64 eV and 1.69 eV, respectively, which is attractive for use as solar cell absorber materials. From first principles study, we find that CZAS exhibits direct band characteristics with a high absorption coefficient of >10 4 cm −1 . Based on energy considerations the stannite structure is found to be more stable than the kesterite, wurtzite, orthorhombic and zinc blende type structures. The total and partial density of states (DOSs) indicate that hybridization between Zn-s and S-p like bands occurs near the Fermi level.